Defining geographic emergency medical services coverage in trauma systems. Issue 1 (July 2019) - Brown, Joshua B.; Rosengart, Matthew R.; Peitzman, Andrew B.; Billiar, Timothy R.; Sperry, Jason L.
Abstract : BACKGROUND: Geographic distribution of trauma system resources including trauma centers and helicopter bases correlate with outcomes. However, ground emergency medical services (EMS) coverage is dynamic and more difficult to quantify. Our objective was to evaluate measures that describe ground EMS coverage in trauma systems and correlate with outcome. METHODS: Trauma system resources in Pennsylvania were mapped. Primary outcome was county age-adjusted transportation injury fatality rate. Measures of county EMS coverage included average distance to the nearest trauma center, number of basic life support and advanced life support units/100 square miles, distance differential between the nearest trauma center and nearest helicopter base, and nearest neighbor ratio (dispersed or clustered geographic pattern of agencies). Spatial-lag regression determined association between fatality rates and these measures, adjusted for prehospital time, Injury Severity Score, and socioeconomic factors. Relative importance of these measures was determined by assessing the loss in R 2 value from the full model by removing each measure. A Geographic Emergency Medical Services Index (GEMSI) was created based on these measures for each county. RESULTS: Median fatality rate was higher in counties with fewer trauma system resources. Decreasing distance to nearest trauma center, increasing advanced life support units/100 square miles, greater distance reduction due to helicopter bases, and dispersed geographic pattern of county EMS agencies were associated with lower fatality rates. The GEMSI ranged from −6.6 to 16.4 and accounted for 49% of variation in fatality rates. Adding an EMS agency to a single county that produced a dispersed pattern of EMS coverage reduced predicted fatality rate by 6%, while moving a helicopter base into the same county reduced predicted fatality rate by 22%. CONCLUSION: The GEMSI uses several measures of ground EMS coverage and correlates with outcome. This tool may be used to describe and compare ground EMS coverage across trauma system geographies, as well as help optimize the geographic distribution of trauma system resources. LEVEL OF EVIDENCE: Ecological study, level IV. Abstract : Supplemental digital content is available in the text.